Excellent Service Strategy to Increase Congregation Satisfaction and Readiness at Sahibuna Sabila Salam Travel in Bukittinggi City - M. Harist Abdullah; Yenty Astarie Dewi; Awaluddin Awaluddin; Khadijah Nurani (Al-Sharf: Jurnal Ekonomi Islam, 2026)
This study aims to analyze the excellent service strategy implemented by Travel Shahibuna Sabila Salam Bukittinggi City in increasing the satisfaction and readiness of Umrah pilgrims, as well as identifying the obstacles faced in its implementation. Using a descriptive qualitative approach, this research was conducted at the Shahibuna Sabila Salam office in Bukittinggi City through interview, observation, and documentation techniques. The results showed that the excellent service strategy implemented includes the five main dimensions of SERVQUAL: responsiveness, reliability, assurance, empathy, and tangibles, which are also supported by sharia values such as amanah, shiddiq, fathanah, and tabligh. Nevertheless, there are obstacles in terms of communication, officer responsiveness, and facilities. Overall, the strategy implemented is proven to significantly increase the satisfaction and readiness of Umrah pilgrims.